Exclusion from school in Scotland and across the UK: Contrasts and questions. (12th July 2019) - McCluskey, Gillean; Cole, Ted; Daniels, Harry; Thompson, Ian; Tawell, Alice
Abstract : This article draws on findings from the first cross‐national study of school exclusion in the four jurisdictions of the UK. It casts new light on the crucial aspects of children's education that lead to school exclusion. It investigates the reasons for the UK disparities, as well as the policy and practice in place. The focus of this article is on a detailed analysis of the policy context in Scotland, where official permanent exclusion reduced to an all‐time low of just five cases in 2014/15. This is much lower than in Northern Ireland and Wales and in stark contrast to England, where exclusions have increased substantially since 2012. Our analysis seeks to understand Scotland's success in reducing exclusion and offers new insight into the ways in which national policies and local factors more generally shape schools and their practices and the consequent impacts for children and young people more broadly in the UK.